Impact Of Leverage And Dividend Policy On Shareholder Wealth On Manufacturing Companies In Indonesia (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
This research discusses the influence of leverage, lagged price ratio, capital gains and return on assets to shareholder wealth in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used in this study was purposive sampling. The sample taken was 5 companies listed on the Indonesia Stock Exchange (IDX) for five years from 2014 to 2018. The dependent variables in the study were shareholder wealth as measured by dividend payout ratio, while the independent variables were leverage, lagged price ratio, capital gain and return on asset. The method used in this study is multiple regression. The results showed that there was no positive influence between leverage, lagged price ratio, capital gains and return on assets on shareholder wealth.